Digital Innovation and Technology Driven Evaluation of Maritime Safety Systems Performance in Indonesia - Retnandari, Septina Dwi; Khaeroman, Khaeroman; Winarni, Aris Toening; Busse, Wolfgang (Aptisi Transactions On Technopreneurship (ATT), 2026)
Maritime safety remains a critical challenge in complex shipping environments, where human error continues to dominate accident causation despite technological advancements. This study aims to evaluate maritime safety system performance in Indonesia through a digital innovation and technology-driven perspective by introducing Adaptive Safety Intelligence (ASI) as an integrative framework linking safety leadership, competency-based training, seafarer well-being, and empowerment. A mixed-methods design combining Structural Equation Modeling (SEM) with qualitative insights was used, involving data from 508 Indonesian seafarers and 30 stakeholders from shipping companies, regulators, and maritime management. The model shows strong validity and reliability, with R² values of 0.878 for ASI, 0.663 for seafarer autonomy and empowerment, and 0.676 for safety performance. The findings empirically confirm ASI as a central mediating construct that translates leadership, training, and well-being into improved empowerment and safety outcomes. This study concludes that maritime safety should be seen as an adaptive, human-centered, and digitally enabled system, emphasizing leadership-driven safety culture, well-being interventions, and integrated maritime systems for strengthening safety governance in Indonesia.